REVIEW OF THE GENUS PHACEPHORUS SCHOENHERR (COLEOPTERA: CURCULIONIDAE: ENTIMINAE) FROM INDIAN SUBCONTINENT - G. MAHENDIRAN; V. V. RAMAMURTHY (The Bioscan, 2013)
The entimine weevil genus Phacephorus Schoenherr (1840) from Indian subcontinent is reviewed. The generic and species description are updated through addition of measurements, description of elytral vestiture and genitalic characters. An annotated checklist and a modified key to the species are also provided.